2023
DOI: 10.1002/pc.27471
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, sound absorption simulation and performance optimization of multi‐layer gradient fiber‐based composites

Abstract: Noise reduction with materials of finite thickness has been a hot research topic. In this study, multi‐layer gradient fiber‐based composites integrating porous, resonant and damping structures were prepared for efficient sound absorption. Here, the effects of composite structure, fiber‐based thickness and micro‐perforated membrane fabric (MPMF) structure on the sound absorption of the composites were investigated. From the results, the sound absorption band of the composite can be effectively tuned by adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Chen et al developed multi-layer gradient fiber-based composites with porous, resonant, and damping structures, achieving a broadband sound absorption coefficient (SAC) of 0.42 [ 23 ]. Khem et al studied the sound absorption capability of oil palm frond (OPF) composites and found that the sound absorption coefficient was proportional to density and improved with alkali treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al developed multi-layer gradient fiber-based composites with porous, resonant, and damping structures, achieving a broadband sound absorption coefficient (SAC) of 0.42 [ 23 ]. Khem et al studied the sound absorption capability of oil palm frond (OPF) composites and found that the sound absorption coefficient was proportional to density and improved with alkali treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These materials mitigate the harm of noise and friction. 1,2 When a viscoelastic polymer (such as rubber, etc.) is stressed near the glass transition temperature (Tg), its segmental movement has obvious hysteresis.…”
Section: Introductionmentioning
confidence: 99%